Spatial analysis of region interaction of West-East corridor's strategic economic area of West Sumatera Province, Indonesia - Siska Amelia; Ernan Rustiadi; Baba Barus; Bambang Juanda (Publisher of Widyagama University of Malang (UWG Press), 2022)
The West-East corridor is one of the main gateways to enter West Sumatra Province. The West-East corridor, which passes through 65 districts, has a variety of potentials and problems. This means, the growth rate of each district will be different. The growth rate and strength of the relationship among regions can be observed through the gravity model's spatial interactions. The gravity model can calculate the relative strength of the relationship between regions. To see the strength of the relationship among regions in the West-East corridor, strategic economic areas were taken into considerations based on their distance and several observational variables, which were the total population variable, infrastructure completeness, level of security, and investment value. Observation analysis units consisted of sixty-five sub-districts along the West-East corridor. Mass 1 (M1) was the central government, West Padang district, and mass 2 (M2) was the other 64 sub-districts. The analysis results show that the total population, infrastructure completeness, level of security, and investment value are not only influenced by their closeness to the government/city center. The infrastructure completeness factor can influence the total population in a region. Likewise, the investment value can be influenced by the infrastructure completeness and the level of security in a region.JEL Classification: O10; R12; R19